Perbedaan Kesiapan Ibu Hamil dalam Menghadapi Persalinan Sebelum dan Sesudah Diberikan Prenatal Yoga di Jagaditha Studio Kabupaten Badung - Ni Made Kartika Apsari; Ni Luh Putu Sri Erawati; Listiana Ade Widya Ningtyas (Poltekkes Kemenkes Denpasar, 2022)
The National Medium-Term Development Plan 2020-2024 is one of the plans to improve access and quality of health services with an emphasis on strengthening basic health services (Primary Health Care). Prevention efforts through promotive and preventive actions to improve maternal health status through prenatal yoga as a complementary therapy. The purpose of this study was to determine differences in the readiness of pregnant women in facing labor before and after being given prenatal yoga at Jagaditha Studio. This type of research is quasi-experimental using a one group pretest posttest design. The study was conducted by Jagaditha Studio in April-May 2022. The sample consisted of 31 pregnant women who never had prenatal yoga. The data are taken by assessing the readiness of pregnant women in facing labor before and after being given prenatal yoga. The respondents have prenatal 60 minutes duration twice a week for two week. The results of Wilcoxon test with p value = 0.000 (0.05). The conclusion is there are differences in the readiness of pregnant women in facing childbirth before and after being given prenatal yoga. Prenatal yoga is recommended to be given in health facilities to help improve the readiness of pregnant women before delivery.